2013
DOI: 10.1080/01691864.2012.703305
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear phase different control for precise output force of bi-articularly actuated manipulators

Abstract: Bi-articular actuators -actuator spanning two joints -play fundamental role in robot arms designed under the human musculoskeletal actuation paradigm. Unlike kinematic redundancy, actuator redundancy resulting from bi-articular actuation brings advantages such as increasing stability, reducing link's inertia, and decreasing non-linearity of the end-effector force with respect to the force direction. The traditional phase different control (PDC) resolves actuator redundancy on the basis of a linearized model de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The muscle forces in the NLPDC are the same as PDC when they are null (0) or maximum [e m i and f m i for i = (1, 2, 3)]. Elsewhere, the muscle forces are calculated on the basis of the robot arm geometry as shown in [24], resulting in …”
Section: E Nonlinear Phase Different Control Approach (Nlpdc)mentioning
confidence: 99%
See 2 more Smart Citations
“…The muscle forces in the NLPDC are the same as PDC when they are null (0) or maximum [e m i and f m i for i = (1, 2, 3)]. Elsewhere, the muscle forces are calculated on the basis of the robot arm geometry as shown in [24], resulting in …”
Section: E Nonlinear Phase Different Control Approach (Nlpdc)mentioning
confidence: 99%
“…The NLPDC is proposed to avoid the calculation error from end-effector force to input torques caused by the linearization process in the PDC [24].…”
Section: E Nonlinear Phase Different Control Approach (Nlpdc)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that, biarticular actuators dramatically increase the range of end effector impedance which can be achieved without feedback [13], increase the capability of path tracking and disturbance rejection, [14] allow for precise output force control [15], and improve balance control for legged robots without force sensors [16]. In addition, biarticularly actuated manipulators produce a maximum output force at the end effector in a more homogeneously distributed way [17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this discharge pattern, a Phase Different Control (PDC) was developed, where a linear muscle activation pattern is modeled based on the electromyography observations of human arm experiments [39]. Later on, the PDC method was improved to be Non-Linear Phase Different Control (NLPDC), which eliminates the error between the calculated muscle activation level and the desired force on the end-effector [40].…”
Section: Introductionmentioning
confidence: 99%